Fluorometric Recognition of Nucleotides within a Water‐Soluble Tetrahedral Capsule. (5th February 2019) - Plajer, Alex J.; Percástegui, Edmundo G.; Santella, Marco; Rizzuto, Felix J.; Gan, Quan; Laursen, Bo W.; Nitschke, Jonathan R.
Abstract: The design of aqueous probes and binders for complex, biologically relevant anions presents a key challenge in supramolecular chemistry. Herein, a tetrahedral assembly with cationic faces and corners is reported that is capable of discriminating between anionic and neutral guests in water. Electrostatic repulsion between subcomponents can be overcome by the addition of an anionic template, or generating a robust covalent framework by incorporating tris(2‐aminoethyl)amine (TREN). The resultant TREN‐capped, water‐soluble, fluorescent cage binds mono‐ and poly‐phosphoric esters, including nucleotides. Its covalent skeleton renders it stable at micromolar concentrations in water, enabling the fluorometric detection of biologically relevant guests in an aqueous environment. Selective supramolecular encapsulants, such as 1, could enable new sensing applications, such as recognition of toxins and drugs, under biological conditions. Abstract : Denk positiv ! Ein fluoreszierender, zwölffach positiv geladener Metall‐organischer Käfig bindet Gastmoleküle in Wasser bei niedrigen Konzentrationen, wobei selektiv Anionen gegenüber ihren neutralen Pendants koordiniert werden. Eine Reihe biologisch relevanter Anionen kann in wässrigen Umgebungen gebunden werden; damit erhält man eine Plattform für das Design und die Verwendung großer Hohlkäfige unter biologischen Bedingungen.